Computational insights into factor affecting the potency of diaryl sulfone analogs as Escherichia coli dihydropteroate synthase inhibitors. (February 2019) - Das, Bratin Kumar; PV, Pushyaraga; Chakraborty, Debashree
Graphical abstract: Highlights: A statistically significant 3D-QSAR model of diaryl sulfone derivatives has been developed. Probable binding and interaction of diaryl sulfone compounds at DHPS catalytic pocket are explored by molecular docking. DFT calculations helped to understand the probable stabilizing factor of the protein-ligand complex affecting biological activity. The computed ΔΔG between most potent and least potent molecules are comparable with experimental result. A10 ns MD simulation was performed to confirm the stability of top scored sulfone compound at the catalytic pocket of DHPS. Abstract: Dihydropteroate synthase (DHPS) is an alluring target for designing novel drug candidates to prevent infections caused by pathogenic Escherichia coli strains. Diaryl Sulfone (SO) compounds are found to inhibit DHPS competitively with respect to the substrate p ABA ( p -aminobenzoate). The extra aromatic ring of diaryl sulfone compounds found to stabilize them in highly flexible p ABA binding loops. In this present study, a statistically significant 3D-QSAR model was developed using a data set of diaryl sulfone compounds. The favourable and unfavourable contributions of substitutions in sulfone compounds were illustrated by contour plot obtained from the developed 3D-QSAR model. Molecular docking calculations were performed to investigate the putative binding mode of diaryl sulfone compounds at the catalytic pocket. DFT calculations were carried out using SCF approach, B3LYP- 6-31 G (d) basis set to compute the HOMO, LUMO energies and their respective location at p ABA binding pocket. Further, the developed model was validated by FEP (Free Energy Perturbation) calculations. The calculated relative free energy of binding between the highly potent and less potent sulfone compound was found to be −3.78 kcal/ mol which is comparable to the experimental value of −5.85 kcal/mol. A 10 ns molecular dynamics simulation of inhibitor and DHPS confirmed its stability at p ABA catalytic site. Outcomes of the present work provide deeper insight in designing novel drug candidates for pathogenic Escherichia coli strains.